PUBLIC RELATIONS AND ADVERTISING: TRENDS, CHALLENGES AND PERSPECTIVES (GYMNASIUM, 2017)
The multitude of the definitions associated with the concept of public relations, the semantic ambiguity of the term of advertising have generated, in the Romanian space, confusions related to public relations and relations with the public, public relations and advertising/publicity. Given these considerations, the aim of the study is to analyze the concept of public relations and publicity/advertising, its defining dimensions, respectively to identify the status of public relations and advertising. As methodology, we opted for a quantitative research by examining the points of view existing in the literature. Based on the essential features and specific differences, aims and objectives, the case study proposes an analysis of the two reference domains, the relations between them, in order to formulate grounded observations regarding the trends, challenges and perspectives associated with them. The hypothesis from which we start is that public relations and advertising can be successfully applied in sport domain, in building and promoting a positive image.